2015
DOI: 10.3329/jdmc.v23i2.25326
|View full text |Cite
|
Sign up to set email alerts
|

Equilibration and Increase of Hemoglobin Concentration after One Unit Whole Blood Transfusion among Patients Not Actively Bleeding

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Conversely, some studies revealed conflicting data [10,11]. A crosssectional study conducted in Bangladesh included 100 patients with a mean age of 24 years and showed a statistically significant difference in the mean increase of Hb at six hours (0.39 g/dl) and 24 h (1.14 g/dl) after transfusion [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, some studies revealed conflicting data [10,11]. A crosssectional study conducted in Bangladesh included 100 patients with a mean age of 24 years and showed a statistically significant difference in the mean increase of Hb at six hours (0.39 g/dl) and 24 h (1.14 g/dl) after transfusion [11].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some studies revealed conflicting data [10,11]. A crosssectional study conducted in Bangladesh included 100 patients with a mean age of 24 years and showed a statistically significant difference in the mean increase of Hb at six hours (0.39 g/dl) and 24 h (1.14 g/dl) after transfusion [11]. However that study used one unit of fresh whole blood as therapy instead of RBC as did some other studies and this may well influence the results as the whole blood would contain plasma which would affect volume distribution in the body [6,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…While measurements at the 12 hours to 24, and 48 hours were in accordance with the hematocrit target of after -transfusion. 10 Another study conducted by Hoque et al, 11 demonstrated Hb at 24 hours after-transfusion, rose more than 1 g/dL in patients without active bleeding. Hoque et al, 11 also stated there was a significant difference in hemoglobin in the examination at 24 hours after-transfusion.…”
Section: Characteristicsmentioning
confidence: 96%
“…10 Another study conducted by Hoque et al, 11 demonstrated Hb at 24 hours after-transfusion, rose more than 1 g/dL in patients without active bleeding. Hoque et al, 11 also stated there was a significant difference in hemoglobin in the examination at 24 hours after-transfusion. Comparison of the Hb's mean before, and 6 hours after-transfusion was statistically significant.…”
Section: Characteristicsmentioning
confidence: 96%
“…As noted by Martinez-Torres et al ., a patient with a hookworm infection can lose up to 0.03 ml, of blood, daily. [ 1 ] Using the referencing data that 1 unit of blood (450 mL) can result in increased 1.14 g/dL hemoglobin,[ 2 ] the mentioned loss due to hookworm infection will result in 0.000076 decreased of hemoglobin per day or 0.00228 decreased of hemoglobin per month. At a time (month), the rate of hemoglobin pool in hookworm infection at that time (H[t]) will be “fixed rate of red blood turnaround value-0.00228t.…”
mentioning
confidence: 99%